Etude de la diversité enzymatique des microorganismes du sol par l'approche métagenomique - Berlemont, Renaud (Universite de Liege, 2009)
Functional metagenomic approach was performed using total environmental DNA extracted from a temperate forest soil sample and from an Antarctica soil sample. Searching for clones harbouring phenotypes related to the production of new hydrolytic enzyme allows the isolation of several new enzymes. Amongst them, an esterase and a cellulase, named RBest1 and RBcel1 respectively, were characterized. By accurate description of their catalytic proprieties these two new enzymes appear to present interesting features. The RBest1 esterase is an enzyme whose activity is stabilised or improved in presence of non water-miscible organic solvent. By sequence analysis, RBest1 is related to other organic solvent tolerant enzyme. Moreover, in aqueous buffer, RBest1 is highly specific for butyrate compound but surprisingly its specificity appears to be shifted in presence of organic solvent. The RBcel1 cellulase, was thoroughly characterized for its involvement both in cellulose degradation and production. Our data highlight the requirement for such enzyme in the bacterial cellulose synthesis process. According to our results, the mining of metagenomic libraries by functional screening associated to detailed description of the isolated enzymes gives hints for both ecological and microbiological questions.